APLIKASI AKRAMIY (Ø£ÙƒØ±Ù…ÙŠ) SEBAGAI MEDIA PEMBELAJARAN BAHASA ARAB - Fitriyah, Khoirun Nisa'il; Noor, Triana Rosalina (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2021)
Arabic is one of the religious subjects that must be taught in in religious schools, starting from the Ibtidaiyah, Tsanawiyah and Aliyah Schools. Arabic is a science that teaches language skills and language skills. So that many students are less interested in learning Arabic because they feel learning Arabic is not easy and less interesting. So that teachers must be more creative in delivering Arabic learning material and even more so during the Covid 19 pandemic which demands all teaching and learning activities through the online system. The purpose of this study was to determine the results of using a new application, namely the Akramiy application (Ø£ÙƒØ±Ù…ÙŠ), an Arabic language learning application that can be accessed via Android and can be downloaded in the Playstore. The method used in this research is descriptive qualitative method and literature study, for data collection techniques through observation, interviews and documentation. This study used XI Grade Students and Arabic Subject Teachers as data sources. Researcher literature study data obtained from studying scientific books and journals in accordance with the research title. The conclusion from the results of this study is the implementation of the Akramiy application (Ø£ÙƒØ±Ù…ÙŠ) as a learning medium for Arabic during the Covid 19 pandemic MA Sabilul Muttaqin Mojokerto makes students more motivated in learning Arabic.